URGENSI ASAS SUBYEK TERITORIAL PADA PEMBERANTASAN KEJAHATAN SIBER - Evi Retno Wulan (Fakultas Hukum Universitas Narotama, 2019)
Establishment and enactment of Law of the Republic of Indonesia No. 11/2008 concerning Information and Electronic Transactions (Statute Book No. 58/2008, Supplement to Statute Book No. 4843, hereinafter abbreviated to Law No. 11/2008) and Law of the Republic of Indonesia No. 19/16 concerning Amendment to Law Number I1 Year 2008 Regarding Information and Electronic Transactions (State Gazette Year 2016 Number 251, Supplement to State Gazette Number 5952, hereinafter abbreviated to Law No. 19/2016), is expected to be able to cope with cybercrime which is increasingly unsettling the public and guaranteeing certainty and use of cyberspace (cyber space) so that it can develop optimally. Provisions governing criminal jurisdiction can be seen in Article 2 and its explanation in Law No. 11/2008